Identification of Therapeutic Targets and Prognostic Biomarkers Among CXC Chemokines in the Renal Cell Carcinoma Microenvironment - Zeng, Qingquan; Sun, Shuolei; Li, Yaxian; Li, Xiaoling; Li, Zuwei; Liang, Hao (Frontiers in Oncology, 2020)
Background: Renal cell carcinoma (RCC) is one of the most common malignances with an ever-increasing incidence and high mortality. Cross-talk between cancer cells and interstitial cells exerts significant effects on neoplasia, and tumor development and is modulated in part by chemokines. CXC chemokines in the tumor microenvironment can modulate immune cell trafficking and regulate tumor cell activities, thus exerting anti-tumor immunological effects and affecting patient outcomes; however, the expression and prognostic values of CXC chemokines in RCC have not been clarified. Methods: ONCOMINE, GEPIA, UALCAN, cBioPortal, GeneMANIA, DAVID 6.8, Metascape, TRRUST, LinkedOmics, and TIMER were utilized in this study. Results: The transcriptional levels of CXCL1/2/5/6/9/10/11/16 in RCC tissues were significantly elevated while the transcriptional levels of CXCL3/ 7 /12/13 were significantly reduced. A significant correlation was found between the expression of CXC1/5/9/10/11/13 and the pathological stage of RCC patients. RCC patients with low transcriptional levels of CXCL1/2/3/5/13 were associated with a significantly better prognosis. The functions of differentially expressed CXC chemokines are primarily related to the chemokine signaling pathway, cytokine-cytokine receptor interactions, and the ILK signaling pathway. Our data suggest that RELA, NFKB1, and SP1 are key transcription factors for CXC chemokines, and the SRC family of tyrosine kinases (LCK, LYN, and FYN), mitogen-activated protein kinases (MAPK1 and MAPK3), and CSNK1D are CXC chemokine targets. We found significant correlations among the expression of CXC chemokines and the infiltration of six types of immune cells (B cells, CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells). Conclusions: Our results may provide novel insights for the selection of immunotherapeutic targets and prognostic biomarkers for renal cell carcinoma.